The Text is a Text is a Text - Dalbello, Marija (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The paper proposed here examines what history of the book can bring to the study of digital literacy. Current scholarly literature on digital text and literacy is multidisciplinary, dispersed in the social sciences and the humanities between the two cultures of research which are difficult to reconcile. A sizable literature in the area of literary studies and rhetoric from the early 1900s added. . .